Behavioral disorders identification, assessment, and instruction of students with EBD - Bakken, Jeffrey P.; Obiakor, Festus E.; Rotatori, Anthony F. (Emerald, 2012)
The area of behavioral disorders is constantly changing and advancing as a result of legislation, new trends, and current research investigations.Currently, there is no comprehensive resource that effectively covers these advances with the breath of topics as this volume. Though it is difficult to keep up with all issues and trends, this volume presents critical topics in all spheres of this area of study.
Keywords: Education -- Special Education -- Learning Disabilities.; Education -- Special Education -- General.; Teaching of specific groups & persons with special educational needs.; Teaching of students with emotional & behavioural difficulties.; Special education.; Behavior disorders in children.; Behavior disorders in adolescence.; elektronické knihy; electronic books